Student Assistance through Training on Javanese Language and Culture at Walailak University Thailand - Andriyanto, Octo Dendy; Panich, Pensri; Septiana, Hespi; Hardika, Meilita; Asrori; Sukarman; Rhubido, Dadang (Jurnal Soeropati, 2024)
The community service activity at the political science study program, Walailak University Thailand has the aim of introducing Javanese language and culture to improve Indonesian insight. The target of this activity is political science students, walailak university who need initial and advanced guidance to improve Indonesian insights. This activity is very helpful for students in providing initial provision before taking a lecture program in Indonesia. This service activity provides theoretical knowledge and cultural practices in the classroom which include the introduction of Javanese language and traditional games. The activity method is carried out with discussions, presentations and cultural practices. The results of the activity showed the enthusiasm of students in learning Javanese language, Javanese culture and Indonesian in general a total of 61% of students stated that they could know Javanese vocabulary, 22% of students knew Javanese culture. 9% of students got preliminary knowledge if they visit Indonesia, while 8% of students got important information related to Javanese culture.